Structural color from solid-state polymerization-induced phase separation. Issue 23 (24th May 2021) - Sicher, Alba; Ganz, Rabea; Menzel, Andreas; Messmer, Daniel; Panzarasa, Guido; Feofilova, Maria; Prum, Richard O.; Style, Robert W.; Saranathan, Vinodkumar; Rossi, René M.; Dufresne, Eric R.
Abstract : Inspired by living organisms that exploit phase separation to assemble structurally colored materials from macromolecules, we show that solid-state polymerization-induced phase separation can produce stable structures at optical length scales. Abstract : Structural colors are produced by wavelength-dependent scattering of light from nanostructures. While living organisms often exploit phase separation to directly assemble structurally colored materials from macromolecules, synthetic structural colors are typically produced in a two-step process involving the sequential synthesis and assembly of building blocks. Phase separation is attractive for its simplicity, but applications are limited due to a lack of robust methods for its control. A central challenge is to arrest phase separation at the desired length scale. Here, we show that solid-state polymerization-induced phase separation can produce stable structures at optical length scales. In this process, a polymeric solid is swollen and softened with a second monomer. During its polymerization, the two polymers become immiscible and phase separate. As free monomer is depleted, the host matrix resolidifies and arrests coarsening. The resulting polymeric composites have a blue or white appearance. We compare these biomimetic nanostructures to those in structurally-colored feather barbs, and demonstrate the flexibility of this approach by producing structural color in filaments and large sheets.